Imaging profiles of Alzheimer's disease and behavioural variant frontotemporal dementia based on cortical structural correlation networks: Brain networks and connectivity. (7th December 2020) - Vuksanovic, Vesna; Staff, Roger; Ahearn, Trevor; Murray, Alison D.; Wischik, Claude
Abstract: Background: Reduced cortical structural properties are recognised as potential imaging marker for neurodegenerative disorders. However, networks of correlated fluctuations in cortical structural properties in Alzheimer's disease (AD) and behavioural variant frontotemporal dementia (bvFTD) have remained elusive. Here, we set out to investigate organisations of structural correlation networks in these patients, and further to show how they become (dis)organised across the cortical lobes. Method: Structural correlation networks are estimated from magnetic resonance images (MRI) in three study groups ‐ AD, bvFTD and healthy controls ‐ each consisting of an equal number of participants (N = 200). Group‐level networks are constructed by cross‐correlating regional structural properties (e.g., thickness, surface area or volume) across all subjects within the group while controlling for confounding variables age, gender and global values. Result: Network organisation is evaluated using several network matrices including the node degree, node strength and network density on the whole‐brain and across the brain lobes. We found that the reduced cortical properties in AD and bvFTD alter organization of the corresponding structural cortical networks at the whole brain. We also found that differences in the measured network properties are lobe specific. Conclusion: Our results show that understanding patterns of correlated reductions in cortical structures may assist in deciphering how cortical changes underlie cognitive and behavioural processes impaired in AD and bvFTD. Reference: Vuksanović V, Staff RT, Ahearn T, Murray AD, Wischik CM. Cortical Thickness and Surface Area Networks in Healthy Aging, Alzheimer's Disease and Behavioral Variant Fronto‐Temporal Dementia. Int J Neural Syst. 2019 Aug;29(6):1850055. https://doi.org/10.1142/S0129065718500557 . Epub 2018 Nov 14. PubMed PMID: 30638083.